The influence of heavy workload on the personal growth of nurses: Tailoring a feasible human resource intervention in the healthcare facilities - Bermillo, Trisha Marie D.; Bustillos, Sciegee G.; Cortez, Maricris L.; Daculan, Jomar P.; De Castro, Marielle Andrea O. 4 0 16; 5
ABSTRACT: Healthcare professionals, especially nurses, face a heightened demand for healthcare services that further intensifies their workload which potentially affects their personal growth. This study seeks to investigate and determine if there is a significant relationship between heavy workload and the personal growth of nurses working in the healthcare facility in Intramuros, Manila. As well as to provide feasible and relevant human resource intervention that will prioritize the nurses well-being. Using a descriptive correlational research design, the study explores the relationship between the variables. Pearson's r Correlation Coefficient is used to measure the degree of association between heavy workload and personal growth. The findings indicate a moderate relationship between the variables (r=0.306), suggesting that an increase in heavy workload corresponds to a decrease in the nurses personal growth. According to the study's findings, the feasible human resource interventions are integrating technology solutions to streamline administrative tasks, implement rewards systems, and provide mentoring programs.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2